Service quality in higher educational institution: an empirical study on academic offices of UiTM Malaysia / Bahijah Md Hashim, Sarina Muhamad Noor and Noraini Aminudin - Md Hashim, Bahijah; Muhamad Noor, Sarina; Aminudin, Noraini (2004)
The Academic Office is responsible for providing services in all matters pertaining to academic affairs for the staff, students as well as the public. Being the heart of the tertiary institution, the service quality rendered by this department has a significant effect on its customers. Thus, this study examines the services it offers by measuring the customers’ feedback. This is done by comparing the customers’ expectations of the service they receive with their perceptions of the actual performance of the department providing the services (Sasser,et.al.,1987; Parasuraman et.al., 1991). The criteria used to assess the service quality covers the organization's tangibility, reliability, responsiveness, assurance and empathy (Parasuraman et. al., 1988; 1985) The scope of this study includes all employees of an academic office, the full-time students enrolled and the lecturers in the institution. The period of the study was from October 2000 until October 2001.The research is based on the Service Quality Model (Parasuraman, Zeithmal and Berry’s Service Quality Model). Information was gathered through a service quality questionnaire (SERVQUAL Quality Questionnaire of Parasuraman, et.al.,1994) which was pilot-tested with a random sample of the respondents. The findings hopefully, will sufficiently guide the administrators in academic offices in planning and outlining approaches and strategies for handling their customers. Besides, it will enable them (the administrators) to take corrective measures or develop new approaches in ensuring the level of service